Diversity and phenetic relationship of lichen genus Usnea in Cisanti Forest area, Bandung District, West Java, Indonesia - JOKO KUSMORO; RAFLI RAIHAN; WAWAN HERMAWAN; RUSDI HASAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kusmoro J, Raihan R, Hermawan W, Hasan R. 2025. Diversity and phenetic relationship of lichen genus Usnea in Cisanti Forest area, Bandung District, West Java, Indonesia. Biodiversitas 26: 583-600. The Cisanti pine forest in Bandung District, West Java, Indonesia, is the area of an educational eco-agrotourism area and is a natural habitat for Usnea. However, there is no report yet about the richness of Usnea in this location that is important to provide information such as its biodiversity and chemical content beneficial resources. This study aimed to explore the diversity and analyze phenetic relationships of Usnea in the Cisanti forest area, based on morphological, anatomical, and chemical characters. The sampling method was carried out by exploring the forest area purposively on pine trees that Usnea grew. Usnea’s phenetic relationship was analyzed using the NTSYS version 2.01e software. The results showed 23 species of Usnea were found, namely U. angulata, U. baileyi, U. barbata, U. ceratina, U. chaetophora, U. cornuta, U. dasaea, U. diffracta, U. flammea, U. flavocardia, U. hirta, U. lapponica, U. maculata, U. mutabilis, U. pangiana, U. robusta, U. rubicunda, U. shimadae, U. sinensis, U. steineri, U. subcornuta, U. subflorida, and U. wasmuthii. Based on the 41 characters analyzed, in general Usnea divided into 3 clusters and cluster separation corresponds with subgenera, namely Usnea, Eumitria, and Dolichousnea. The closest relationship is between U. sinensis and U. maculata, and between U. barbata and U. lapponica by a similarity index of 0.814. The most distant relationship is between U. baileyi and U. barbata and between U. angulata and U. chaetophora, as well as U. subcornuta and U. pangiana by a similarity index of 0.616.